Lexical and semantic skills of fourth grade students used in communication by writing - Danuta Piórkowska-Poniewierska; Marta Bogdanowicz; Paweł Andrzej Atroszko (Maria Curie-Skłodowska University, Lublin, Poland, 2020)
The aim of this paper is to provide some explanation for one of the main reasons of school failure, namely the problems with creating written expressions. The conducted study included 301 students of fourth grade, age of 10. The properties and application of lexical-semantic aspect of written expressions were described. The written works of students were submitted to a detailed analysis concerning the number of used words and categories of used lexemes. The material was analyzed quantitatively and subsequently described and interpreted. On the basis of the results,a developmental trajectory of lexical and semantic categories formation in written communication was suggested. The level of lexical correctness was established, and significant relationships with properly used vocabulary were identified. Furthermore, the directions for future studies and analyses emerged from the results of the current study.